The optimizing the use of Tiktok to increase sales of Medan Pancing Culinary MSMEs - Mica Siar Meiriza; Raja Satrio Pandiangan; Sastra Sefina Sitanggang; Yohana Br Sinaga; Grace Anna Maria Sitanggang; Nazwa Arifa; Sabrina Theresia Sukma; Irvan Aldi Josua Marpaung; Robin Cornelius Siahaan; Robema Natalia Nainggolan; Karisa Kusumadewi Saputri; Marsha Astrid Exelsia Hutasoit; Nabila Hidayanti; Nielsen Samuel Panahatan Siagian; Al Ikhwan; Ramadhan Pulungan (Universitas Nusa Cendana, 2026)
This study examines the utilization of TikTok as a digital marketing platform to enhance sales performance and brand awareness among culinary Micro, Small, and Medium Enterprises (MSMEs) in the Medan Pancing area. Employing a descriptive qualitative approach, data were collected through semi-structured interviews with culinary MSME owners to explore both the opportunities and challenges associated with TikTok adoption. The findings indicate that TikTok provides an effective and low-cost marketing channel through its algorithm-driven content distribution, interactive features, and broad audience reach. MSMEs that consistently produced creative and authentic content reported improved brand visibility and increased sales performance. However, limited digital literacy, low confidence in content creation, inadequate understanding of platform analytics, and rapidly evolving content trends remain major barriers to effective utilization. The study further identifies digital skills training, collaboration with local content creators, and the adoption of user-friendly content production tools as practical strategies to accelerate digital transformation among MSMEs. These findings highlight TikTok's strategic role in strengthening customer engagement and business competitiveness while contributing to the growing literature on digital marketing and MSME development in emerging economies. Future research is encouraged to employ quantitative or mixed-method approaches to examine the long-term impact of social media marketing on MSME performance across different business sectors. Keywords: TikTok Marketing; Culinary MSMEs; Digital Promotion; Sales Growth